Analysis of Digital Da'wah Ideology on Social Media: A Case Study of Preaching Actors on Youtube - Khotimah, Nurul; Supena, Ilyas; Amin, Nasihun; Putra, Pandika Adi; Setyawan, Ari (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This study analyzes the ideology of digital preaching on YouTube delivered by Ustaz Firanda Andirja, Ustaz Abdul Somad, Ustaz Adi Hidayat, and Emha Ainun Nadjib (Cak Nun). Using a Social Network Analysis (SNA) approach, the research explores the social dynamics emerging from interactions in the comment sections of their preaching videos. The findings identify four dominant ideologies: literalist Islamism, which creates schisms in contextual and ethical preaching elements (Ustaz Firanda Andirja); nationalist Islamism, which causes schisms in contextual and comparative elements (Ustaz Abdul Somad); modernist Islamism, which generates schisms in historical elements (Ustaz Adi Hidayat); and conservative Islamism, which triggers schisms in contextual and ethical elements (Emha Ainun Nadjib). This study demonstrates that digital preaching content not only reflects the ideologies of the preachers but also significantly influences public opinion on social media. The findings highlight the importance of understanding ideological dimensions in digital preaching to address social dynamics more effectively.